Epidemiological and clinical characterization of notified cases of viral hepatitis in the municipality of Cacoal-RO: a time-frame from 2018 to 2020 (Research, Society and Development, 2022)
Viral Hepatitis, an aggravation of compulsory weekly notification, presents specific tropism for hepatocytes, diverse viral etiologies, inflammatory character and broad clinical spectrum. Due to the amount of its prevalence, facing it represents a public health challenge. It aimed to explain the clinical and epidemiological profile of hepatitis notifications in the municipality of Cacoal-RO during the period 2018-2020. This is a cross-sectional epidemiological study of a descriptive and quantitative nature, through the analysis of secondary data, not requiring the approval of CONEP/CEP, extracted from the notification form of the Notifiable Diseases Information System (SINAN), of the Department of Informatics of the SUS (DATASUS), making a temporal cut in relation to the variables of interest. Between 2018 and 2020, 93 cases were reported in the municipality, of which 55 (59.14%) were male. There was a predominance of brown races, with 62 (66.67%) cases. As for education, 5th to 8th grades had 17 (18.28%) of the notifications. The 40-59 age group obtained 43 (46.24%) communications. Among the clinical variables, etiologically, the B virus prevailed, with 75 (80.65%) cases, in addition to the chronic/carrier form being present in 91 (97.85%) of those affected. Regarding transmission, it was predominantly sexual, with 76 (81.72%) cases. As for confirmation, 75 (80.65%) were HBsAg reagents and 17 (18.28%) were positive for AntiHCV. In this way, the epidemiological and clinical profile of the notifications is evident, which contributes to the planning and adoption of health education measures aimed at local needs.